Birmingham Royal Orthopedic Hospital (BROH) CAM Offset: A Simplified Metric for Detection of CAM Morphology of the Hip - Gavvala, Sai Niharika; Shirodkar, Kapil; Hussein, Mohsin; Jenko, Nathan; Iyengar, Karthikeyan P.; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2025)
CAM morphology of the hip is a disorder of abnormal morphology of the femoral head–neck junction associated with loss of the osseous sphericity of the femoral head. Several radiological measurements exist to detect CAM morphology of the hip.The aim of the study was to evaluate the precision and efficacy of a new BROH CAM offset distance as a novel magnetic resonance imaging (MRI) parameter designed to detect CAM morphology of the hip.Oblique axial MR images of 100 patients who underwent hip MRI scans were analyzed. Two readers measured the alpha angle and BROH CAM offset to detect CAM morphology. Diagnostic cutoff values for cam offset measurements were determined, and their diagnostic accuracies were evaluated.The mean “alpha angle” measured on an oblique projection was 34.31 degrees (standard deviation [SD] = 14.63), and when measured on an axial projection, it was 41.98 degrees (SD = 7.44). The BROH CAM offset distance was 3.49 mm (SD = 0.90 mm). There was an excellent correlation between the new BROH CAM offset and the alpha angle with a p-value of 0.006 (Pearson's linear correlation coefficient). Based on the results, a 57-degree alpha angle correlates to a BROH CAM offset of 4.11 mm, a 60-degree alpha angle correlates to a BROH CAM offset of 4.23 mm, and a 55-degree alpha angle correlates to a BROH CAM offset of 4.03 mm.Our new BROH CAM offset shows an excellent correlation with the alpha angle and is the easiest metric that can be used for the detection of CAM morphology of the hip.
Keywords: CAM morphology; alpha angle; femoroacetabular impingement; magnetic resonance imaging